Analysis of chlorophenols in environmental water using polydopamine‐coated magnetic graphene as an extraction material coupled with high‐performance liquid chromatography. Issue 9 (13th April 2016) - Ye, Qing; Liu, Linhai; Chen, Zongbao; Hong, Liming
Abstract : In this work, polydopamine‐coated magnetic graphene nanocomposites were synthesized by a simple solvothermal reaction and self‐polymerization of dopamine, and the as‐made nanocomposites were successfully applied as an effective adsorbent for the preconcentration of the four chlorophenols in environmental water samples before high‐performance liquid chromatography. The polydopamine‐coated magnetic graphene nanocomposites have several advantages such as a high surface area, fast separation ability, super‐hydrophilicity, and high peak intensities for aromatic analytes. Various parameters, including eluting solvent and volume, the amounts of absorbents, extraction time and elution time were optimized. Validation experiments showed that the optimized method had good linearity ( r 2 > 0.9990), satisfactory precision (RSD < 6.7%) and high recovery (90–105%). The limits of detection were 0.013–0.020 μg/L and the limits of quantification ranged from 0.043 to 0.070 μg/L. The results indicated that the proposed method had advantages of convenience, good sensitivity, and high efficiency. The method has been applied successfully to analyze chlorophenols in real water samples.